THE EFFECT OF AUDITOR SWITCHING AND PROFITABILITY ON AUDIT REPORT LAG WITH THE AUDIT COMMITTEE AS A MODERATING VARIABLE - Sri Wahyuni Zanra; Zubir Zubir (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to examine and analyze the effect of auditor switching, company size and profitability on audit report lag with audit committee as moderating variable. This study uses quantitative methods.The population of this study is companies in the consumer goods industry sector, hotels, restaurants and tourism sub-sector companies and transportation sub-sectors listed on the Indonesia Stock Exchange in 2016-2020, totaling 149 companies. Sampling was done by purposive sampling method so that a sample of 41 companies was obtained. Data analysis using multiple linear regression analysis and moderated regression analysis with absolute difference value approach.The results of the study indicate that auditor switching and company size do not affect audit report lag. Profitability has a negative effect on audit report lag. The audit committee is unable to strengthen or weaken the effect of auditor switching, company size and profitability on audit report lag.